2016
DOI: 10.1590/2179-8087.102714
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da Temperatura e do KNO3 na Germinação de Acnistus arborescens (Solanaceae)

Abstract: RESUMOA propagação de Acnistus arborescens (fruto-do-sabiá) usualmente é feita através de estacas, devido a baixa taxa de germinação de suas sementes. O objetivo deste trabalho foi estudar o efeito da temperatura e do estimulante nitrato de potássio (KNO 3 ) na germinação do fruto-do-sabiá. O experimento foi realizado utilizando quatro regimes de temperatura (20, 25, 30 e 20-30 °C), com e sem nitrato de potássio, em delineamento inteiramente casualizado com quatro repetições de 50 sementes cada. Foram avaliado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
(22 reference statements)
0
2
0
2
Order By: Relevance
“…This saline substance acts on positive photoblastic seeds, and its effect is related to the disinhibition of the pentose-phosphate cycle (Gupta, 2002). Brito et al (2016) found the efficiency of KNO3 for Acnistus arborescens, as this method increased the rate of germination, being indicated to raise the vigor of the seeds. According to the authors, this result may be related to the fact that this substance increases the respiratory rate of the seed.…”
Section: Chemical Scarification As a Technique For Overcoming Tegumen...mentioning
confidence: 96%
“…This saline substance acts on positive photoblastic seeds, and its effect is related to the disinhibition of the pentose-phosphate cycle (Gupta, 2002). Brito et al (2016) found the efficiency of KNO3 for Acnistus arborescens, as this method increased the rate of germination, being indicated to raise the vigor of the seeds. According to the authors, this result may be related to the fact that this substance increases the respiratory rate of the seed.…”
Section: Chemical Scarification As a Technique For Overcoming Tegumen...mentioning
confidence: 96%
“…Es importante tener en cuenta en la aplicación de tratamientos pregerminativos o de osmoacondicionamiento de semillas, que la disponibilidad de agua y concentración de iones, se debe mantener en niveles adecuados, con el fin de controlar los procesos de hidratación y que la solución osmótica active el metabolismo, puesto que si el potencial osmótico es demasiado bajo, la germinación se detiene, y por lo tanto, la protrusión de la radícula no ocurre (Mora et al, 2004). El efecto del nitrato de potasio en diferentes concentraciones como tratamiento pregerminativo de semillas se ha evaluado en especies como agraz (Magnitskiy y Ligarreto, 2007), tomate (Moreno y Jiménez, 2013), chile ancho (Cortez et al, 2011) y especies silvestres (Freire de Brito et al, 2016). También se han encontrado resultados positivos al realizar tratamiento pregerminativo de los bulbos de Gladiolus alatus, una especie floral cultivada a nivel mundial, al aplicar con una solución de 1% de KNO 3 con la que se obtuvo un 80% de germinación (Ramzan et al, 2010) .…”
Section: Variable Ecuación Unidadunclassified
“…It grows quickly, facilitating the establishment of other species that require shading areas, thus being important for the ecological succession. In addition, it has a huge using potential in carbon compensation projects and its seeds present physical dormancy, which allows them to remain inactive in the seed bank, an important strategy for the population dynamics (Silva et al, 2015;Marcos 2 Although seed dormancy works as an efficient mechanism to ensure the species survival, it also may be a barrier for the propagating plants with economic interest (Brito et al, 2016). Physical dormancy is common in forest species, and different methods can be used in order to overcome it, such as the immersion in hot water and the mechanical or acidic scarification (Guedes et al, 2013;Barbedo & Santos Júnior, 2018).…”
Section: Introduction and Objectivesmentioning
confidence: 99%